Mataram Cultural Tourism Model Based on Interactive Digital Tourism Map User Experience (UX) - Prabowo , Agung; Simanjuntak, Oliver Samuel (RSF Conference Series: Business, Management and Social Sciences, 2021)
This study aims to design a tourism navigation innovation using the Interactive Digital Tourism Map in the former Mataram Kingdom. This innovation is the development of the Bantul Exploration tourism application which is expected to become a tourism icon in Bantul Regency. This map is needed to provide comprehensive information for potential tourists. This map makes it easier for potential tourists to plan their trips through the information provided on this map. In the first stage, this research designs a prototype Digital Tourism Map. This article discusses the User Experience (UX) of this map. The method used is Expert Review, which is asking an expert in application design to provide a review on this application. The results of the review state that this application has conceptually fulfilled the user's information needs. The available menus are also considered quite complete, which include (a) the location of tourism objects and the location of public facilities supporting tourism; (b) information in the form of content related to communicative and interesting tourism objects, (c) tourist travel paths from the starting point of tourists to tourism objects. . However, the information material is still lacking and less interesting. It should be packaged in the form of a story telling.